2015
DOI: 10.1016/j.joca.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Association of adipokines and joint biomarkers with cartilage-modifying effects of weight loss in obese subjects

Abstract: Adiponectin and leptin may be associated with cartilage loss. Further work will determine the relative contributions of metabolic and mechanical factors in the obesity-related joint changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Metabolites characteristics including energy metabolism and lipid and carbohydrate metabolism in the OA patients' synovial tissue cultures were significantly decreased compared with those with little or no evidence of the disease [23, 24]. Obesity increased mass and joint load and altered proinflammatory factor adipokines secretion, leading to the chronic low grade inflammatory status in joint tissues [25, 26]. Additionally, cholesterol accumulation in the cartilage can impair the efflux function of cartilage, hence inducing OA [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites characteristics including energy metabolism and lipid and carbohydrate metabolism in the OA patients' synovial tissue cultures were significantly decreased compared with those with little or no evidence of the disease [23, 24]. Obesity increased mass and joint load and altered proinflammatory factor adipokines secretion, leading to the chronic low grade inflammatory status in joint tissues [25, 26]. Additionally, cholesterol accumulation in the cartilage can impair the efflux function of cartilage, hence inducing OA [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ku et al and Karvonen-Gutierrez et al reported that SF and serum leptin levels are directly correlated with the radiographic severity of OA [141, 142] and also with proinflammatory cytokines, MMP-1, and MMP-3 levels in OA patients, suggesting the possible use of leptin as a potential biomarker for quantitative detection of OA severity. In a recent study, SF leptin concentrations were associated also with knee and hip pain in OA patients [140, 143, 144]. In addition, in Chinese population, serum levels of leptin were independently associated with increased knee cartilage volume assessed by radiography [145].…”
Section: Adipokines In the Pathobiology Of Osteoarthritic Cartilagementioning
confidence: 99%
“…A lower leptin : adiponectin ratio correlated with lower knee OA pain [143]. Furthermore, it has determined that weight loss is associated with an increase in adiponectin and a decrease in leptin and cartilage oligomeric matrix protein plasma levels in obese subjects [144]. This suggests that lower levels of adiponectin are related to a more aggressive disease and that higher levels have anti-inflammatory properties.…”
Section: Adipokines In the Pathobiology Of Osteoarthritic Cartilagementioning
confidence: 99%
“…While a number of biomarker studies have focused on the release of cartilage matrix proteins such as collagens, proteoglycans, or cartilage oligomeric matrix protein in the serum and synovial fluid567, mounting evidence suggests that OA is more than just cartilage wear and tear, as both systemic and local intra-articular metabolic factors such as inflammation appear to play a pivotal role in joint degeneration89. Thus, in addition to matrix degradation products, inflammatory cytokines and adipokines may also have potential as OA biomarkers that are related to disease mechanisms1011.…”
mentioning
confidence: 99%